2004
DOI: 10.1207/s15327612jamd0802_1
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Iterative Alternative to Ordinal Log-Linear Models

Abstract: Abstract. Log-linear modeling is a popular statistical tool for analysing a contingency table. This presentation focuses on an alternative approach to modeling ordinal categorical data. The technique, based on orthogonal polynomials, provides a much simpler method of model fitting than the conventional approach of maximum likelihood estimation, as it does not require iterative calculations nor the fitting and re-fitting to search for the best model. Another advantage is that quadratic and higher order effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 22 publications
(54 reference statements)
1
22
0
Order By: Relevance
“…Note the squaring of σ I and σ J . Similarly, the MNI estimate (eqn 26) should be while the BDNI estimate (eqn 25) is and coincides exactly with the original non‐iterative parameter estimate derived by Beh & Davy (2004). In the original paper, the R code used to calculate the estimates of this parameter using Newton's method and the three non‐iterative procedures reflects the corrected versions of the estimates stated here and is therefore true and correct.…”
supporting
confidence: 53%
“…Note the squaring of σ I and σ J . Similarly, the MNI estimate (eqn 26) should be while the BDNI estimate (eqn 25) is and coincides exactly with the original non‐iterative parameter estimate derived by Beh & Davy (2004). In the original paper, the R code used to calculate the estimates of this parameter using Newton's method and the three non‐iterative procedures reflects the corrected versions of the estimates stated here and is therefore true and correct.…”
supporting
confidence: 53%
“…It failed because of the two zero cell values, although this problem was easily overcome by adding 0.05 to each cell. Beh & Davy (1998, 1999, 2004) indicated that BDNI estimation provides a satisfactory means of estimating the parameter φ. The findings discussed in confirm these initial results.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach to parameter estimation for ordinal log‐linear models is to consider the non‐iterative, or direct, estimation procedure described by Beh & Davy (1998, 1999, 2004). These authors introduced a non‐iterative method of estimating the parameter φ and demonstrated, by way of applications, that the procedure produces very similar results obtained using Newton's method.…”
Section: The Basics Of Log‐linear Modelsmentioning
confidence: 99%
See 2 more Smart Citations